RANCANG BANGUN SISTEM INFORMASI APLIKASI PENGELOLAAN KAS BERBASIS WEBSITE (STUDI KASUS : KOMUNITAS OJEK ONLINE LAGON SETIA) - Dede Imana Yulianto; Gustin Triani; Saprudin (OKTAL : Jurnal Ilmu Komputer dan Sains, 2024)
The Lagon Online Ojek Community has carried out its functions and roles in cash management. But they still need an information system because until now it is still conventional. So it is difficult to provide transparent information about cash management in community financial reporting. The design of this website-based system was created to make it easier for community treasurers to convey community financial information to members, to design a system that is easy to use and can carry out accurate data collection. This system is designed to contain position data, user data, member data, cash data, expenditure data, print reports, cash history, expenditure history. The tools used to build this system use the PHP programming language with a MySQL database